2007
DOI: 10.1002/adsc.200600436
|View full text |Cite
|
Sign up to set email alerts
|

Silica‐Alumina‐Supported, Tungsten‐Based Heterogeneous Alkane Metathesis Catalyst: Is it Closer to a Silica‐ or an Alumina‐Supported System?

Abstract: Grafting of [W(C‐t‐Bu)(CH2‐t‐Bu)3] (1) on silica‐alumina partially dehydroxylated at 500 °C generates a surface complex [(SiO)W(C‐t‐Bu)(CH2‐t‐Bu)3] (2) as evidenced by mass balance analysis, IR, and NMR spectroscopy. Upon treatment of this species under H2, a tungsten hydride derivative, [(SiO)(EO)W(H)x] (3), (E=Si or Al), is formed. Both of these complexes are active as alkane metathesis catalysts. The activity of this hydride is similar to that observed for the tungsten hydride‐supported on alumina and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
82
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(88 citation statements)
references
References 25 publications
4
82
0
2
Order By: Relevance
“…The complex grafted onto alumina is active in propane metathesis (turnover number [TON] = 28), whereas that grafted onto silica is not (TON = 0) [10,13,14]. Recently, it was shown that a silica-alumina support, treated under similar conditions, yields a very similar surface complex as silica, with grafting onto the Si atom (Si s O)W(Ct Bu)(CH 2 t Bu) 2 but, surprisingly, gives a propane metathesis reactivity similar to that on the alumina support [15]. The influence of the support thus seems especially confused.…”
Section: Introductionmentioning
confidence: 86%
“…The complex grafted onto alumina is active in propane metathesis (turnover number [TON] = 28), whereas that grafted onto silica is not (TON = 0) [10,13,14]. Recently, it was shown that a silica-alumina support, treated under similar conditions, yields a very similar surface complex as silica, with grafting onto the Si atom (Si s O)W(Ct Bu)(CH 2 t Bu) 2 but, surprisingly, gives a propane metathesis reactivity similar to that on the alumina support [15]. The influence of the support thus seems especially confused.…”
Section: Introductionmentioning
confidence: 86%
“…[38] Recent experimental data have revealed that the primary products of the reaction are olefins and dihydrogen; thus, a mechanism invoking tantalum carbenes and a metallocyclobutane intermediate, as observed in olefin metathesis, is proposed (Scheme 2), [28] which shows the bifunctional role of the tantalum hydrides acting as both dehydrogenation and olefin metathesis catalysts. While both recent reports [39,40] and initial work on alkane metathesis [41] (also referred to as "molecular redistribution reaction of alkanes") always involved a dual catalyst system (see Figure 3 for selected examples), the systems developed by SOMC for alkane metathesis [42][43][44] originate from a single system {either [Ta(=CH-tBu)(CH 2 -tBu) 3 or W(ϵC-tBu)(CH 2 -tBu) 3 ]}, each grafted on the appropriate inorganic oxide. The alumina-supported tungsten system is particularly noteworthy, as it achieves high activities in alkane metathesis.…”
Section: Reactivity Of Silica-supported Tantalum Hydrides With C-h Anmentioning
confidence: 99%
“…[4] This final tantalum-based system, which contains at least the two surface tantalum hydride species, [(ϵSiO) 2 TaH] and [(ϵSiO) 2 TaH 3 ], [5] has displayed remarkable activity toward C-C and C-H bonds in both stoichiometric activation [6] and catalytic reactions such as alkane metathesis, [7] crossmetathesis between ethane and toluene, [8] and methane coupling to form ethane. [4] [a] Université de Lyon, Institut de Chimie de Lyon UMR 5265 (CNRS -CPE Lyon -Université Lyon 1) Bâtiment 308 F, 43 Boulevard du 11 Novembre 1918, 69616 Villeurbanne, France E-mail: quadrelli@cpe.fr studies show the relevance of tantalum carbenes and Chauvin-like metallacyclobutane intermediates in most of these reactions. Finally, the stoichiometric N 2 cleavage and NH 3 activation to the final imido amido tantalum(V) complex [(ϵSiO) 2 Ta(NH)(NH 2 )] (3) are reviewed and discussed mechanistically.…”
Section: Introductionmentioning
confidence: 99%
“…On silica sintering is observed and TEM shows that tungsten particles (size 0.1-0.2 nm) are formed [71]. On alumina no sintering is observed and a hydride species is obtained [71,73]. This hydride species is characterized by a small peak at 10.0 ppm in 1 H MAS NMR and by two infrared bands at 1903 and 1804 cm −1 .…”
mentioning
confidence: 92%
“…In contrast to complexes 18 and 19 formed on silica, complex 20 has a good activity in propane metathesis at 150°C with an initial TOF equal to 1.8 h −1 [73]. The mechanism of this reaction Alkenesinvolves three steps: dehydrogenation of the alkane, olein metathesis, and hydrogenation of the resulting olein.…”
mentioning
confidence: 99%